IMPLEMENTASI SISTEM PENJAMINAN MUTU INTERNAL DI SEKOLAH TINGGI ILMU EKONOMI MUHAMMADIYAH MAMUJU - Muhammad Ferils; Syafaruddin Syafaruddin (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2020)
SPM DIKTI is a systemic activity to improve the quality of universities in a planned and sustainable manner, while the goal is to ensure the fulfillment of higher education standards so as to develop a culture of quality in Indonesian universities. The Internal Quality Assurance System is implemented with the aim of maintaining and improving the quality of higher education in a planned and sustainable (continuous iamprovement). This research aims to find out how the implementation of the internal quality assurance system and the role of implementing resources in building quality culture in STIE Muhammadiyah Mamuju. This research was conducted at the Quality Assurance Institute using qualitative methods with data collection techniques through observation and in-depth interviews to the quality assurance implementing resources of STIE Muhammadiyah Mamuju. The results of this research show that the implementation of the internal quality assurance system in STIE Muhammadiyah Mamuju is carried out in order to build a quality culture. its implementation refers to law number 12 of 2012 on higher education, article 52 paragraph (3) then derived through permenristekdikti number 44 year 2015 on national standards of higher education and permenristekdikti number 62 of 2016 on the quality assurance system of higher education, as well as guidelines for the internal quality assurance system of the Diktilitbang Assembly pp Muhammadiyah, its stages by completing the structure of the SPMI document (quality policy, quality manual, quality standards , and a quality form) then designs the plan operationally through the SPMI (PPEPP) cycle. The result of the implementation of SPMI is the assessment of external parties (BAN PT) both accredited study programs B, but can not be said to meet the standards due to budget constraints, lack of commitment of leaders in building a culture of quality, as well as the lack of certified auditors owned by LPM. Keywords: Implementation, Policy, Manual, Quality Standard